Comparative FISH-mapping of TTAGG telomeric sequences to the chromosomes of leafcutter ants (Formicidae, Myrmicinae): is the insect canonical sequence conserved? - Carini Picardi Moraes de Castro; Danon Clemes Cardoso; Ricardo Micolino; Maykon Passos Cristiano (Comparative Cytogenetics, 2020)
Telomeric sequences are conserved across species. The most common sequence reported among insects is (TTAGG)n, but its universal occurrence is not a consensus because other canonical motifs have been reported. In the present study, we used fluorescence in situ hybridization (FISH) using telomeric probes with (TTAGG)6 repeats to describe the telomere composition of leafcutter ants. We performed the molecular cytogenetic characterization of six Acromyrmex Mayr, 1865 and one Atta Fabricius, 1804 species (Acromyrmex ambiguus (Emery, 1888), Ac. crassispinus (Forel, 1909), Ac. lundii (Guérin-Mèneville, 1838), Ac. nigrosetosus (Forel, 1908), Ac. rugosus (Smith, 1858), Ac. subterraneus subterraneus (Forel, 1893), and Atta sexdens (Linnaeus, 1758)) and described it using a karyomorphometric approach on their chromosomes. The diploid chromosome number 2n = 38 was found in all Acromyrmex species, and the karyotypic formulas were as follows: Ac. ambiguus 2K = 14M + 12SM + 8ST + 4A, Ac. crassispinus 2K = 12M + 20SM + 4ST + 2A, Ac. lundii 2K = 10M + 14SM + 10ST + 4A, Ac. nigrosetosus 2K = 12M + 14SM + 10ST + 2A, and Ac. subterraneus subterraneus 2K = 14M + 18SM + 4ST + 2A. The exact karyotypic formula was not established for Ac. rugosus. FISH analyses revealed the telomeric regions in all the chromosomes of the species studied in the present work were marked by the (TTAGG)6 sequence. These results reinforce the premise that Formicidae presents high homology between their genera for the presence of the canonical sequence (TTAGG)n.